A cultural lens on Yucatec Maya families' COVID‐19 experiences. Issue 5 (26th August 2021) - Alcalá, Lucía; Gaskins, Suzanne; Richland, Lindsey E.
Abstract: Health guidance during the COVID‐19 pandemic led families around the world to spend more time isolated together, disrupting leisure activities, schooling, social interactions, and family work (UNICEF, 2021). Using the lens of Yucatec Maya families' cultural values and practices, semi‐structured interviews were conducted with 18 Yucatec Maya rural women in Mexico ( M age = 32; and for comparison, 13 middle‐class European‐American women ( M age = 41)), with children 6–7 years old, to analyze families' experiences during the pandemic. Faced with the same isolation as in the United States, our exploratory analysis revealed Maya families experienced external stresses but at the same time were generally comfortable with their children's everyday activities and their social‐emotional well‐being, illuminating consequences of the communities' cultural theories about development.